2019
DOI: 10.5603/pjnns.a2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors of angiography headache and evaluation of its relationship to primary headaches

Abstract: Introduction. Angiography headache is defined as a new headache caused directly by cerebral angiography. We aimed to investigate the prevalence and clinical characteristics of angiography headache, and its relationship with primary headaches.Material and methods. This single-centre prospective cohort study was carried out in our tertiary healthcare centre. Patients who had undergone a diagnostic cerebral angiography procedure between March 2016 and June 2017 were included in the study. During and after the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 14 publications
(25 reference statements)
3
8
0
Order By: Relevance
“…We propose to change the definition of "occurring later, but within 24 hours" to "occurring later, but within 1 week after angiography". Patients with history of headache are more likely to have angiography headache has been established in previous and our studies [2][3][4][5][6]20]. In our study, the history of headache was a risk factor for angiography headache.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We propose to change the definition of "occurring later, but within 24 hours" to "occurring later, but within 1 week after angiography". Patients with history of headache are more likely to have angiography headache has been established in previous and our studies [2][3][4][5][6]20]. In our study, the history of headache was a risk factor for angiography headache.…”
Section: Discussionsupporting
confidence: 71%
“…The possible explanation is that women demonstrating lower pain thresholds and the fluctuations of sex hormones especially estrogen and progesterone may cause a change in the prevalence or intensity of headache [1,18,19]. Previous history of headache as a risk factor for angiography headache had been established in many studies [2][3][4][5][6]20]. The possible mechanism maybe that some individuals with a history of headache had lower thresholds for trigeminal activation [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study [5] included 327 patients of whom 55.6% developed AH, mainly with a previous history of headaches. In the light of known reports, the current work [1] is of considerable value -the study group consisted of 226 patients and the frequency of AH was found to be 22%. The authors define the AH risk group as female, higher educated patients with a previous history of primary headache.…”
mentioning
confidence: 84%
“…The literature has relatively few investigations of AH and its risk factors. Female sex was associated with AH in the study of Gil-Gouveia et al, 2 Aktan et al, 7 and Demir et al 6 Among the studies that found an association between AH and previous history of headaches, we name Ramadan et al, 5 Aktan et al, 7 and Demir et al 6 Regarding demographic factors, a higher education level was associated with AH in the publications of Kwon et al 4 and Demir et al 6 …”
Section: Introductionmentioning
confidence: 97%
“…In the literature, reports of its frequency are highly variable (0.3 to 55.6%). 2 3 4 5 6 It is usually underestimated by neuroradiologists, possibly due to its usually benign and transient character. Nonetheless, in our clinical practice, we see that patients with a previous history of AH tend to be resistant to performing new cerebral DSAs.…”
Section: Introductionmentioning
confidence: 99%